2002
DOI: 10.1021/ie010901w
|View full text |Cite
|
Sign up to set email alerts
|

Supported Liquid Membrane-Based Pervaporation for VOC Removal from Water

Abstract: Supported liquid membrane pervaporation (SLMPV) is a pervaporation process for separating volatile organic compounds (VOCs) from their dilute aqueous solutions through a supported liquid membrane. It integrates simultaneous extraction of the VOCs from the aqueous solution with vacuum stripping of the VOCs from the organic phase in one membrane module. Using a liquid membrane consisting of nonvolatile hydrocarbons immobilized in the micropores of hydrophobic porous polypropylene hollow fibers with or without a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…These recent efforts have resulted in improving the stability of ILMs for gas separation tremendously; the ILMs formed were tested for a few months without any loss of stability or performance. Similarly, the approach of using non‐volatile solvents/carriers was equally successful in developing highly VOC‐selective ILMs for VOC removal from gas streams18 and aqueous streams 19. For example, trichloroethylene (TCE) was removed from aqueous streams using hexadecane immobilized liquid membrane in a membrane‐based pervaporation technique using an ultrathin silicone rubber‐coated microporous hollow fiber membrane.…”
Section: Stability Of Ilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…These recent efforts have resulted in improving the stability of ILMs for gas separation tremendously; the ILMs formed were tested for a few months without any loss of stability or performance. Similarly, the approach of using non‐volatile solvents/carriers was equally successful in developing highly VOC‐selective ILMs for VOC removal from gas streams18 and aqueous streams 19. For example, trichloroethylene (TCE) was removed from aqueous streams using hexadecane immobilized liquid membrane in a membrane‐based pervaporation technique using an ultrathin silicone rubber‐coated microporous hollow fiber membrane.…”
Section: Stability Of Ilmsmentioning
confidence: 99%
“…For example, trichloroethylene (TCE) was removed from aqueous streams using hexadecane immobilized liquid membrane in a membrane‐based pervaporation technique using an ultrathin silicone rubber‐coated microporous hollow fiber membrane. The TCE and water fluxes were studied for a period of four months and were essentially stable 19…”
Section: Stability Of Ilmsmentioning
confidence: 99%
“…Numerous studies on the applications of SILM in pervaporation http for the separation of organic compounds from dilute aqueous solutions have been reported [8][9][10][11][12][13][14]. Although the use of SILM is always associated with an instability problem caused by the leaching of the liquid membrane from the porous support, particularly under high pressure or vacuum conditions, several methods have been proposed to overcome this limitation, and these include reimmobilisation of the liquid membrane [15], surface coating [16], and mixing with a base polymer to form a thin, stable film [17]. In addition, the use of a porous support with a smaller pore diameter would also help enhance the SILM stability [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Pervaporation is one of these membrane separation techniques, being noted as an advantageous method for the separation of azeotropes and volatile organic compound/water mixtures 5–8. Many studies have reported the removal of VOCs from water through various polymer membranes using pervaporation 9–12…”
Section: Introductionmentioning
confidence: 99%